Addition of zirconium oxide to Biodentine increases radiopacity and does not alter its physicochemical and biological properties - Ochoa-Rodríguez, Victor Manuel [UNESP]; Tanomaru-Filho, Mario [UNESP]; Rodrigues, Elisandra Marcia [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Spin-Neto, Rubens; Faria, Gisele [UNESP] (FapUNIFESP (SciELO), 2019)
Objectives: To evaluate the radiopacity of Biodentine (BD) and BD associated with 15% calcium tungstate (BDCaWO4) or zirconium oxide (BDZrO2), by using conventional and digital radiography systems, and their physicochemical and biological properties. Materials and Methods: Radiopacity was evaluated by taking radiographs of cement specimens (n=8) using occlusal film, photostimulable phosphor plates or digital sensors. Solubility, setting time, pH, cytocompatibility and osteogenic potential were also evaluated. Data were analyzed using one-way ANOVA and Tukey post-test or two-way ANOVA and Bonferroni post-test (α=0.05). Results: BD radiopacity was lower than 3 mm Al, while BD ZrO2 and BD CaWO4 radiopacity was higher than 3 mm Al in all radiography systems. The cements showed low solubility, except for BDCaWO4. All cements showed alkaline pH and setting time lower than 34 minutes. MTT and NR assays revealed that cements had greater or similar cytocompatibility in comparison with control. The ALP activity in all groups was similar or greater than the control. All cements induced greater production of mineralized nodules than control. Conclusions: Addition of 15% ZrO2 or CaWO4 was sufficient to increase the radiopacity of BD to values higher than 3 mm Al. BD associated with radiopacifiers showed suitable properties of setting time, pH and solubility, except for BDCaWO4, which showed the highest solubility. All cements had cytocompatibility and potential to induce mineralization in Saos-2 cells. The results showed that adding 15% ZrO2 increases the radiopacity of BD, allowing its radiography detection without altering its physicochemical and biological properties.
Keywords: Dental cements; Dental digital radiography; Endodontics; Materials testing; Physicochemical analysis